THE INFLUENCE OF INITIAL IRRIGATION ON THE GROWTH OF TWO HYBRIDS OF EUCALYPTUS - de Oliveira Costa, Carla Deisiane; da Silva Lopes, Adriano; Rosalvo Melgar Brito, Kelvin; Dionisio de Andrade, Vinicius; Batista Viana, Carlos Diogo; Gomes Xavier, Thiago Augusto (Floresta, 2018)
In order to maximize the productivity of forest species, techniques such as irrigation have been used. The objective of this study was to evaluate the water use efficiency and the influence of the irrigation located in the growth of the hybrids of eucalyptus Grancam and Urograndis at 65 months. The study was carried out in the experimental area of the State University of Mato Grosso do Sul (UEMS), in Aquidauana (state of Mato Grosso do Sul, Brazil). The experimental design was randomized blocks with subdivided plots. The treatments used in the plots were two irrigation systems (microsprinkler and drip) and one control treatment with no irrigation (dryland), and in the subplots, the two hybrids of eucalyptus: Grancam (Eucalyptus grandis x Eucalyptus camaldulensis) and Urograndis (Eucalyptus urophylla x Eucalyptus grandis), submitted to irrigation up to the 53° month after planting (MAP). The results were submitted to the analysis of variance and the Tukey test for means comparisons at 5% of probability. The use of irrigation in eucalyptus i nfluences the productivity, providing increased wood volume, height of plants and diameter at breast height (DBH). The hybrid Grancam showed greater increase in height, and Urograndis increased in DBH. The higher efficiency of water use for the volumetric production of wood was observed in drip irrigation for the hybrid Grancam. The hybrid Urograndis is more efficient in the use of water for the volumetric production of wood regardless of the treatment.